2019
DOI: 10.1111/cen.13913
|View full text |Cite
|
Sign up to set email alerts
|

Brown adipose tissue thermogenesis in polycystic ovary syndrome

Abstract: Summary Objective Polycystic ovary syndrome (PCOS) is associated with increased obesity with a greater propensity to weight gain and a lack of sustainable lifestyle interventions. Altered brown adipose tissue (BAT) thermogenesis is a potential contributor to obesity in PCOS. BAT activity and modulation have not been studied in PCOS. This observational study explored BAT thermogenesis and its associations in women with and without PCOS. Participants and methods Cutaneous temperature was recorded from supraclavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 48 publications
2
23
0
Order By: Relevance
“…The positive effects of spironolactone-inducing CXCL14 in differentiated adipocytes are also consistent with previous reports indicating that spironolactone induces adipose tissue browning in rodents16 and activates brown fat in humans 17. Recent reports disclosed impaired BAT activity in PCOS subjects6 7 and the capacity of brown fat activation to ameliorate PCOS in experimental models 8. Considering that CXCL14 is preferentially released by brown adipocytes,2 it may be speculated that SPIOMET treatment drives a shift in adipose tissue plasticity to a more brown/beige phenotype resulting in enhanced CXCL14 release, potentially improving glucose homeostasis and possibly reducing diabetes risk.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The positive effects of spironolactone-inducing CXCL14 in differentiated adipocytes are also consistent with previous reports indicating that spironolactone induces adipose tissue browning in rodents16 and activates brown fat in humans 17. Recent reports disclosed impaired BAT activity in PCOS subjects6 7 and the capacity of brown fat activation to ameliorate PCOS in experimental models 8. Considering that CXCL14 is preferentially released by brown adipocytes,2 it may be speculated that SPIOMET treatment drives a shift in adipose tissue plasticity to a more brown/beige phenotype resulting in enhanced CXCL14 release, potentially improving glucose homeostasis and possibly reducing diabetes risk.…”
Section: Discussionsupporting
confidence: 89%
“…However, the specific cellular and tissue targeting, and the relative role of each of the SPIOMET components in the context of PCOS is poorly understood. It has been recently reported that women with PCOS have lower brown adipose tissue (BAT) activity as compared with healthy controls,6 7 and experimental data suggest that BAT activation might be a promising therapeutic option for PCOS 8…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first study that evaluated BAT activity and anatomical distribution in women with PCOS using 18 F-FDG PET-CT. However, a recent study detected lower skin temperature at supraclavicular region in women with PCOS, which also suggests lower BAT activity compared to controls (38). Based on studies involving other metabolic diseases, we hypothesized that BAT activity might be lower in women with PCOS.…”
Section: Discussionmentioning
confidence: 85%
“…Women with PCOS demonstrate diminished lipid oxidation [151] as a component of metabolic inflexibility [152], and exhibit lower lipid oxidation-dependent thermogenesis [153], all contributing to increased obesity, adipogenic constraint-enhanced hyperlipidemia and insulin resistance [154], pancreatic beta cell decompensation and T2D [155]. Enhanced adrenergic (sympathetic nervous system noradrenalin) stimulation of visceral fat lipolysis compounds a hepatic hyperlipidemic environment [156].…”
Section: Metabolic Pcos-related Traits In Macaque Modelsmentioning
confidence: 99%